Methods of pretreatment and their impacts on anaerobic codigestion of multifeedstocks: A review. (24th October 2021) - Rabii, Anahita; Koupaie, Ehssan Hosseini; Aldin, Saad; Dahman, Yaser; Elbeshbishy, Elsayed
Abstract : Abstract: Anaerobic codigestion (AnCoD) has attracted attention owing to its advantages over conventional anaerobic digestion, and attempts are still going on to develop methods for improving the efficiency of this technology. Mostly, addition of cosubstrates without applying a proper pretreatment cannot adequately enhance the performance of the digestion. However, there is a lack of a comprehensive study on different pretreatment methods specific to the wide range of cosubstrates. This review aimed to (i) categorize pretreatment techniques that have been developed for improving AnCoD, (ii) present the results of the studies on the effect of pretreatment on improving AnCoD, and (iii) provide a comparison between pretreatment methods and their application for different types of cosubstrates. The findings primarily validated the influence of pretreatment to enhance the process by increasing biodegradability, improved hydrolysis, reduced hydraulic retention time (HRT), and improved methane production. The five main categories of pretreatment employed in codigestion included the following: mechanical, thermal, chemical, biological, and hybrid pretreatment. Among them, mechanical and biological pretreatment have the most and least application in codigestion, respectively. Greater efforts are required on the application of biological pretreatment and cost–benefit analysis of different pretreatment options on the variety of the cosubstrates. Practitioner Points: Pretreatment can significantly enhance biomethane production in anaerobic digestion Anaerobic codigestion along with pretreatment can further enhance the conventional anaerobic digestion of single feedstock Mechanical and biological methods have been the most and least practiced pretreatment options Selection of applicable pretreatment option to enhance methane production is subject to the type of cosubstrates in the system There is a research gap in evaluating the application of biological pretreatment for various types of cosubstrates Abstract : This study shows different categories of pretreatment techniques that have been developed for improving anaerobic codigestion. It summarizes the effect of each technique on increasing biodegradability, improved hydrolysis, reduced HRT, and improved methane production and provides a comparison between the methods and their application for different types of cosubstrates. The five main categories of pretreatment employed in codigestion included mechanical, thermal, chemical, biological, and hybrid pretreatment.